Investigation on the stability of the Enol Tautomer of Favipiravir and its derivatives by DFT, QTAIM, NBO, NLO and 1H-NMR - Zaki Safi; Nuha Wazzan (Journal of Taibah University for Science, 2023)
Relative stability energies of enol and keto forms of Favipiravir drug (6-fluoro-3-hydroxy-2-pyrazine carboxamide) and its twelve derivatives were theoretically envisaged using the B3LYP/6-311 + G(3df,2p)//B3LYP/6-311 + G(d,p) level of theory. Influence of the nature of the substituted groups on the geometric structures, IMHB, vibrational frequencies, dipole moments, and global reactivity descriptors was systematically studied. The enol form was found to be more stable than the keto form, regardless of the nature of the substituted group, by an average of 12.5 and 5.4 kcal/mol in the gas phase and in the aqueous solution, respectively. The role of the IMHB strength in the stability of the enol form compared with the keto form was investigated in terms of QTAIM and NBO analysis and 1H NMR chemical shifts. The NLO properties at CAM-B3LYP with 6-311 + G(d,p) basis set of the two forms and their derivatives were also used to explain the relative stability.